Analisis Efektivitas IPAL Produksi Industri PT. X di Sidoarjo dalam Menurunkan Beban Pencemar pada Air Limbah Industri. - Budi Samodra, Mula Rangga; Fadhil, Muhammad Faisal (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The animal feed industry generates wastewater from boiler operations, vehicle disinfection activities, and laboratory processes. Wastewater from these sources contains TDS, TSS, pH, ammonia, fluoride, Biochemical Oxygen Demand (BOD), and Chemical Oxygen Demand (COD), which have the potential to pollute the environment. PT X, as one of the animal feed industries, operates a Wastewater Treatment Plant (WWTP) to ensure that the discharged wastewater complies with applicable regulations and is therefore environmentally safe. This study aims to evaluate the effectiveness of the WWTP at PT X using a quantitative method with descriptive analysis. The results indicate that the WWTP at PT X is still operating effectively in reducing most pollutant parameters. However, for one parameter, fluoride, the removal performance is only at a “moderately effective” level. Therefore, to improve the effectiveness of fluoride removal, one recommended approach is to replace the flow system of the coagulant and flocculant dosing tank with a dosing pump. Dosing pumps provide a more stable and effective delivery of coagulants and flocculants.